2010
DOI: 10.1158/0008-5472.can-10-0621
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Infection and Reinfection in Adult Women: the Role of Sexual Activity and Natural Immunity

Abstract: There is paucity of data on whether or not women can be re-infected with human papillomavirus (HPV) types to which they were exposed earlier in life and on the role of natural immunity. The observation of HPV infection at older ages may be explained by reactivation of a latent infection or new exposure from sexual activity. Our objective was to analyze the association between re-infection and sexual activity. We analyzed data from 2462 women enrolled in the Ludwig-McGill cohort and followed every 4-6 months fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
133
4
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(142 citation statements)
references
References 23 publications
4
133
4
1
Order By: Relevance
“…Some studies observed a reduced risk of subsequent HPV infection in anti-HPV seropositive individuals (25)(26)(27). However, findings have been inconsistent (24,28,29) and the immune correlate (i.e., the antibody level which results in effective immunity) is unknown. Antibody levels elicited after HPV vaccination are 1 to 4 logs higher than after natural infection and have been shown to be highly protective against incident infection with vaccine-type HPV (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies observed a reduced risk of subsequent HPV infection in anti-HPV seropositive individuals (25)(26)(27). However, findings have been inconsistent (24,28,29) and the immune correlate (i.e., the antibody level which results in effective immunity) is unknown. Antibody levels elicited after HPV vaccination are 1 to 4 logs higher than after natural infection and have been shown to be highly protective against incident infection with vaccine-type HPV (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…Population studies from various parts of India found increased HPV prevalence as age advances (Sankaranarayanan et al, 2005;Asiaf et al,2012;Srivastava et al, 2012). Highest HPV prevalence occurs soon after initiation of sexual activity among young women in the age group of 18-24 years and gradually comes down with a second peak after the fifth decade of life (Trottier et al, 2010). In this context WHO recommendation of screening of women 35 years or above and every five years for three tests in life time will be a more cost effective approach in resource poor settings (Aggarwal, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence shown that re-infection with HPV (with a different or either a same genotype) is a common occurrence (Trottier et al, 2010). Prior infection with HPV does not provide women with adequate immunity against subsequent infections.…”
Section: Prevalence Incidence Duration Co-infection and Re-infectionmentioning
confidence: 99%
“…Moreover, it has been shown that an infection with a specific genotype does not decrease the probability of being infected by a phylogenetically-related genotype (Thomas et al, 2000). Recent studies have shown that re-infection with a same genotype, as well as incident infection in older women who had multiple lifetime sexual partners, are associated with new sexual partners suggesting that infection in adult women may results not only from reactivation (infections acquired at a young age that never completely cleared but become undetectable and appeared later in life) but also from new exposure via sexual activity (Trottier et al, 2010;Munoz et al, 2004).…”
Section: Prevalence Incidence Duration Co-infection and Re-infectionmentioning
confidence: 99%